Pathologies En-Route of Oral Basaloid Malignancies to Basaloid Squamous Cell Carcinoma - Mehendiratta, M; Rehani, S; Kumra, M; Shah, MK (Kathmandu University Medical Journal, 2015)
Accurate histopathological diagnosis of any tumour is imperative because of variable prognostic and clinical implications. Basaloid squamous cell carcinoma (BSCC) is a rare distinctive histological variant of oral squamous cell carcinoma (OSCC) exhibiting an aggressive clinical course and poor prognosis. The advanced stage of presentation is speculatively responsible for this biological behaviour which is manifested by development of metastasis and subsequently poor survival. However, the non-specific clinical appearance and histopathological resemblance of BSCC with OSCC and other oral basaloid malignancies (OBM) especially in limited sample size poses diagnostic difficulties. The article emphasizes on the diagnostic criteria and pitfalls encountered in making the differential diagnosis of BSCC from OBMs along with report of a case presented at a dental college in January 2012. Kathmandu University Medical Journal Vol.12(2) 2014: 141-145